Rancang Bangun Sistem Informasi Transaksi Penjualan Pada Kedai Sompo Coffee Berbasis Web - Mohammad Dzaky Risqullah; Fitri Yanti (CV. Multi Kreasi Media, 2023)
Kedai Sompo Coffee is a shop that sells various kinds of food and beverages, which is located on Jl. Maulana Hasanudin No. 6 Rt 02 Rw 07 Poris Jaya, Tangerang City. This Sompo Coffee shop still encounters several problems, one of which is the sales system that still uses a manual system, from inputting products to making reports. Likewise, in examining sales transactions that occur every day, all sales notes must be collected according to the date of the transaction, because they have not used the facilities effectively and efficiently. By applying information technology is expected to facilitate the sales process both from the consumer and employees, especially in terms of calculations and report generation.